Evaluasi Pengakuan dan Pengukuran Berbasis Akrual Atas Penerimaan Negara Bukan Pajak (PNBP) Berjenis Pelayanan - Rio Christanto; Nanda Ayu Wijayanti (Politeknik Ganesha Medan, 2023)
This study aims to evaluate the phenomenon of accrual-based recognition and measurement using the date point of the Consular Function official memorandum document on non-tax state revenue (PNBP) of service type at the Ministry of Foreign Affairs of the Republic of Indonesia based on public accountability framework and cost benefit analysis and. Accrual-based recognition and measurement using these documents causes the value of revenue-LO presented in the Financial Statements to be over or understated as it consists of 5 (five) frequencies or periods of recognition and measurement, namely every day, every week, every two weeks, every month, and every three months. The unit of analysis is in the form of multiple units of analysis in five work units of the Indonesia Representative Diplomatic Mission which represent each period of recognition and measurement. This research is descriptive qualitative research. Data were obtained through interviews and documentation. The data analysis method uses qualitative descriptive techniques and content analysis. The results show that accrual-based recognition and measurement of PNBP type services not only pay attention to the occurrence but also the completion of the service process. In addition, the recognition and measurement treatment carried out so far has considered the aspects of costs and benefits so that there are five recognition and measurement periods. In the future, it is hoped that there will be an integrated system so that the frequency of recognition and measurement can be uniform.